2011
DOI: 10.1590/s1415-790x2011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de bebidas alcoólicas na população adulta Brasileira: características sociodemográficas e tendência

Abstract: Objective: To estimate the prevalence of alcohol consumption, identify the associated sociodemographic characteristics in 2006, and evaluate consumption trends from 2006 to 2009. Methods: We evaluated 54,369 adults living in the 26 Brazilian state capitals and the Federal District. Usual consumption was related to drinking at least one dose of alcohol in the past 30 days, and binge consumption meant 5 or more doses for men and 4 or more for women at least once in the past 30 days. Results: The usual consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 16 publications
3
27
0
15
Order By: Relevance
“…Other studies within adults have also identified greater alcohol abuse in younger age brackets 3,39,40 , corroborating the current study. This characteristic may be explained by the birth cohort effect, since society has proven to be more permissive towards alcohol consumption 33 , and by the social and cultural stimulus acting on the age group: participation in parties and events and advertising campaigns targeting this audience 41 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies within adults have also identified greater alcohol abuse in younger age brackets 3,39,40 , corroborating the current study. This characteristic may be explained by the birth cohort effect, since society has proven to be more permissive towards alcohol consumption 33 , and by the social and cultural stimulus acting on the age group: participation in parties and events and advertising campaigns targeting this audience 41 .…”
Section: Discussionsupporting
confidence: 91%
“…A study of data from the VIGITEL survey for the overall Brazilian population 40 and a study on the population of the city of São Paulo 44 found that marriage/stable union was a protective factor against alcohol abuse in both genders, even after adjusting for other variables 40 . These differences suggest that the relationship between alcohol consumption and conjugal status, plus the other socio-demographic characteristics, require further research in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, measures are recommended to make it less available, such as price increases, advertising bans, and restriction of times and places of sale 32 . In Brazil, abusive consumption of alcoholic beverages is high and is more frequent in men and in the young population 33,34 . Tobacco used to be among the major RFs; however, the burden attributable to smoking has been decreasing due to the decline in its prevalence in Brazil 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This paper also contributes to the discussion on exploring alcohol use in detail when investigating cardiac risk, both in clinical practice and research. Heavy alcohol use is a concern for violent deaths in Brazil and a recent survey has shown an increase in this pattern of alcohol use (Moura & Malta, 2011). The potential association with higher cardiac disease risk emphasizes the need for understanding this problem in detail and to alert public policy makers about the need for effective control of alcohol consumption in Brazil.…”
Section: Discussionmentioning
confidence: 99%